#TITLE_ALTERNATIVE# - Aditya Wardhana (NIM 132 03 080), Reza
Abstract: Transmit diversity is more applicative for cellular downlink communication compared to receive diversity. Those due to transmit diversity only need single antenna receiver, while receive diversity should use two or more antenna receiver which separated far enough to give adequate cross correlation. Diversity technique self is expected not merely for improving signal quality, but also can accommodate high transmission rate. From the background of above, this final project research is done to give performance comparison of several Space-Time Block Code(STBC)-based transmit diversity which give maximum transmission rate and works for complex modulation. Those method are: Simple Transmit Diversity (STD), Extended-Alamouti (EA), Quasi Orthogonal Space Time Block Code (QOSTBC), and Quasi Orthogonal Space Time Block Code (QOSTBC) with phase rotation.. Simulation made using QPSK modulation and assumed that separation between each transmit antenna is quite far. Therefore, independent Jakes fading model is used. Systems performance is measured by BER versus SNR curve. From evaluation result, STD gives significant performance improvement compared to system without diversity by employing slight complexity addition. Using more antennas, EA and QOSTBC did not give significant improvement from STD. Whether antenna separation and device complexity are not counted as evaluation parameter, QOSTBC with phase rotation expressed finest performance within other transmit diversity methods.